New earthworm species of Righiodrilus (Clitellata, Glossoscolecidae) from eastern Amazonia - Santos, Bianca Tamires Silva Dos; Bartz, Marie Luise Caroline; Hernández-García, Luis Manuel; Rousseau, Guillaume Xavier; Martins, Marlucia Bonifácio; James, Samuel Wooster (Zootaxa, 2017)
Three new species of the glossoscolecid earthworm genus Righiodrilus are described from material collected in northern Pará and Maranhão States, Brazil. Rhigiodrilus gurupi n. sp. is characterized by four pairs of post-testicular spermathecae in xiv–xvii. Rhigiodrilus viseuensis n. sp. is distinguished by tubercula pubertatis in xix–xxiii and clitellum in xvi–xxiii. Rhigiodrilus moju n. sp. is the only species in the genus that lacks tubercula pubertatis. We provide an updated key and a distribution map for all species of Righiodrilus.